The Mechanism for Calculating the Nishab of Zakat for Civil Servants’ Income According to MUI Fatwa No 3 Year 2023 - Asri, Juinda; Supardi, Supardi; Setiawan, Adi; Afrianty, Nonie (EKOBIS SYARIAH, 2024)
Civil servants are one of the subjects of zakat, which is called income zakat, and each zakat is issued if it has reached the nishab. The Indonesian Ulema Council regulates zakat in the MUI Fatwa Number 3 of 2003 concerning Zakat Income. The UPZ of the Regional Office of the Ministry of Religion of Bengkulu Province takes zakat on income every month from all groups of civil servants, even though some of the income of certain groups of civil servants has not reached the nishab. Determining the income nishab value is based on the Decree of the Chairman of BAZNAS No. 14 of 2021 concerning the income and services zakat nishab in 2021. The income nishab value is 85 grams of gold multiplied by IDR. 938,099,- amounting to Rp. 79,738,415,-. The research method used is descriptive analytical method with a qualitative approach. The results of this research show that: 1) the calculation of the zakat nishab on civil servant income applied by UPZ at the Regional Office of the Ministry of Religion of Bengkulu Province is taken from the basic salary of civil servants which is then paid out at 2.5% every month. 2) The calculation of the zakat nishab on civil servants' income by UPZ at the Regional Office of the Ministry of Religion of Bengkulu Province is not in accordance with MUI Fatwa Number 3 of 2003 because zakat is imposed on all groups of civil servants, zakat is taken from all gross income, and zakat is issued even though it has not yet reached the haul time.